PENGARUH VARIASI DOSIS PUPUK ORGANIK LIMBAH CAIR NANAS (LCN) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA - Muarif, Moh; Sujarwanta, Agus; Santoso, Handoko; Muhfahroyin, Muhfahroyin (BIOLOVA, 2021)
Abstract: This research is an experimental research, which aims to determine the effect of variation dosage in of organic pineapple liquid waste fertilizer, on the growth and productivity of red lettuce (Lactuca Sativa L) and its potential as learning resources of biology learning. This research uses a Completely Randomized Design with 1 control and 3 treatment combinations and 5 repetitions. This research was conducted for 30 days. The parameters which is used in this research include plant height and wet weight of lettuce (Lactuca sativa L), with supporting data in the form of number of leaves and stem diameter. The main data is tabulated and analysed using the SPSS 25.0 application which includes Multivariate Analysis of Variance. The results of this research can be concluded that the application of organic fertillizer from pineaplle liquid waste has a significant influence on the growth and product of lettuce (Lactuca sativa L). The results of the research be used as a practical guide on plant growth and development materials.